PEMBELAJARAN LITERASI KEBENCANAAN BERBASIS DIGITAL BAGI REMAJA DI DAERAH TERPENCIL: DIGITAL-BASED LEARNING OF DISASTER LITERATURE FOR YOUTH IN REMOTE AREA - jaenal mutakim (Program Studi Manajemen Pendidikan, 2021)
This study aims to develop a conceptual digital literacy learning for adolescents in remote communities; Designing digital literacy learning activities for youth in remote communities; and knowing the evaluation of digital literacy learning This research procedure was carried out by adapting the ILDF (Integrated Learning Design Framework) development procedure model. This model consists of three stages, namely Explorating, Enactment and Evaluation. This research was conducted in Pabuaran Village, Sukamakmur District, Bogor Regency.for adolescents in remote communities.The step of the development model begins with exploring, at this stage the developer identifies the need for distance learning due to the large number of trainees who experience difficulties in participating in learning activities in face-to-face, especially for teenagers who live in remote areas, the selection of the Moodle platform, this is because Moodle has an application in the form of Moodle Mobile which can be accessed via android phone. In the Enactment stage, at this stage the developer begins to design disaster literacy learning using the Mobile Modeling Model, compile prototypes and develop the learning in detail. The last stage is Evaluation, Testing material experts and media experts. Material experts give the results of the percentage of the feasibility of learning materials of 93.75%. Media testing gives the results of the feasibility percentage of 79.9%. The test on the small group test of the trainees got a result of 86.97% which means it is very feasible to use. This study provides suggestions that facilities and infrastructure must be available properly. The required facilities such as an adequate and stable internet network and an android phone with a minimum android version of Lollipop that must be owned by all disaster literacy training participants.